Blended learning as a form of language education for university students - Ludmila Yu. Kaplina; Arina V. Banartseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper investigates the effectiveness of blended learning through analyzing students characteristic, background, learning outcomes. It is aimed at predicting the blended learning effectiveness taking student characteristics as independent variables. Such concepts as e-learning, synchronous and non-synchronous technologies are determined in the paper as important parts of blended learning. Our survey was administrated to gather data on student characteristic/background and learning outcomes. The final evaluation results were used as a measure for performance as an outcome. We applied a learning questionnaire and the results showed the effectiveness of blended learning design (on-line tools, technology quality) and student characteristics (intrinsic motivation, self-regulation and satisfaction).